Factors Associated with the Presence of Extraintestinal Manifestations in Patients with Ulcerative Colitis in a Latin American Country - Jesús K. Yamamoto-Furusho (Inflammatory Intestinal Diseases, 2020)
Background and Aim: Ulcerative colitis (UC) is a subtype of inflammatory bowel disease that can develop extraintestinal manifestations (EIMs) in a subgroup of patients. The aim of this work was to study the frequency and clinical factors associated with the development of EIMs. Methods: We evaluated a total of 260 Mexican patients with confirmed UC who were followed retrospectively in order to identify the factors associated with the presence of EIMs. Results: The frequency of EIM was 55.8%. The factors associated with the development of EIM were pancolitis (p = 0.003, OR = 2.44, 95% CI = 1.34–4.56) and previous colectomy (p = 0.024, OR = 7.54, 95% CI = 1.20–60.44). A clinical course of initial activity and then long remission for >5 years was found to be a protective factor (p = 0.002, OR = 0.31, 95% CI = 0.14–0.67). Conclusion: The frequency of EIM was 55.8% in our population, and the factors associated with their development were pancolitis and colectomy; meanwhile, a clinical course of initial activity and then long remission was a protector feature.